The Role of Herd Behaviour in Determining the Investor’s Monday Irrationality - Rayenda Brahmana,; Chee Wooi Hooy,; Zamri Ahmad, (Asian Academy of Management Journal of Accounting and Finance, 2012)
With regards to determining whether herding is spontaneous and irrational behaviour causing the Day-of-the Week Anomaly, this paper intersects the Christie and Huang (1995) herd behaviour model with French’s (1980) Day-of-the Week model in several layers of tests. We use firm-level data and investigate the return dispersion of 846 Bursa Malaysia stocks during 1990-2010. This paper found the herd behaviour is the determinant for investor’s Monday irrationality, especially in small caps industry.